ALAT PROYEK MIKRO KONTROL PENGHAPUS PAPAN TULIS OTOMATIS MENGGUNAKAN REMOTE BERBASIS ARDUINO - Ragil Pamungkas, Sukma; Mukhlison, S.T., M.T; Sri Widoretno, S.T., M.T (Jurnal Qua Teknika, 2023)
The development of automation technology on blackboard erasers can increase the level of hygiene and health, because with an automation system the activity of erasing the blackboard can be carried out automatically without inhaling marker ink which has an impact on health and does not dirty hands. The purpose and working mechanism of making an automatic blackboard eraser using a remote and Arduino. The method of designing an automatic whiteboard eraser is made using an arduino uno as a microcontroller and an infrared remote that controls a stepper motor to drive the eraser. The assembly of the blackboard eraser mechanism is done by preparing a blackboard prototype that has been mounted on an iron frame. Then, install the top rail and bottom rail. Followed by installing the upper and lower wheels on the upper and lower rails that have been glued to the eraser clamp. The results of the design of an automatic whiteboard eraser based on Arduino Uno, can facilitate teachers and students in the learning process. The conclusion of this design is that the automatic whiteboard eraser can work according to the program that has been entered into the arduino uno and is controlled by an infrared remote and the whiteboard eraser working mechanism functions properly to erase the marker ink on the blackboard with a power of 26.67 watts.